A personal computer based monitoring system for safe grain storage - Jain, S K; Sivadasan, K; Murty, S N; Rai, A K (Journal of Agricultural Engineering, 2000)
Temperature and moisture are the two important parameters which affect the growth of insects, fungi and micro-organisms in stored grains. The present paper describes the construction of suitable sensors for on-line monitoring of grain moisture and grain temperature inside the storage structures. A personal computer based system consisting of 13 channels has been developed for monitoring grain temperature and grain moisture at different locations within a storage structure together with ambient temperature. On the basis of the parameters monitored, the system evaluates the status of storage and displays whether the storage is safe or not.